Pioneers, Refugees, Exiles, and Transnationals: Gendering Diaspora in an Ethno-Religious Context - Epp, Marlene (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
AbstractThis paper examines four women who immigrated to Canada within diasporas originating in disparate times and places: an Amish woman escaping persecution in Bavaria in the early nineteenth century; a woman displaced from Ukraine during the Second World War; a political exile from Central America in the 1980s; and a contemporary transnational migrant with homes in Canada and Mexico. While they all identify with a particular ethno-religious community, the Mennonites, their commonalities rest more on similar experiences of uprooting and settlement, as well as their familial roles. In the case of each story, the diasporic experience de-stabilized gender identities and revealed the mutability of ethno-religious markers. The paper suggests that frameworks of diaspora and transnational movement offer a better way to understand the gendered experiences of these women, rather than traditional ideological and progressive concepts of migration.